Hanna Szumańska-Grossowa wspomina Konstantego Ildefonsa Gałczyńskiego - Mitzner, Piotr (Poznańskie Studia Polonistyczne. Seria Literacka, 2023)
The article discusses Hanna Szumańska-Grossowa’s reminiscences about Konstanty Ildefons Gałczyński, their personal contacts, the poet’s musical taste, and his alcohol addiction.